Economic Growth Analysis of Six Divisions of Bangladesh Using Location Quotient and Shift-Share Method - Islam, Faisal Bin; Mubassirah, Fabiha Atique; Siddiq, Fariba; Hossain, Dipita; Sharmin, Nusrat; Haque, Afsana (Journal of Bangladesh Institute of Planners, 2015)
The structure and performance of industrial sectors of a region is an impelling factor in determining the growth of a region’s economy. In Bangladesh, a great heterogeneity in economic growth exists among different regions along with the administrative divisions. This study investigates the short run and long run spatio-temporal variation of regional economies of the six divisions of Bangladesh. Location Quotient and Shift share method have been employed with gross divisional product and gross domestic product at constant price for the year 1995-96 to 1999-2000 as parameter. The comparative analysis of the six divisions reveals that Fishing and Construction sector have been the most flourishing industries and Real Estate, Renting and Business activities has been lagging for all the six divisions during the timeframe. Barisal district is in economic malaise relative to the other divisions and hence requires special attention to be in pace of consistent economic growth. Journal of Bangladesh Institute of Planners, Vol. 8, Dec 2015, pp. 135-144